India, Germany and Europe. A Spatial Perspective at SDG 11 on Sustainable Cities and Communities. - Binot, Regine; Debnath, Tania; Kar, Biswajit; Kundu, Debolina; Milbert, Antonia; Mishra, Rakesh; Müller, André; Schmidt-Seiwert, Volker (My University, 2020)
Responding to crucial challenges in urban and rural development the United Nations decided on the New Urban Agenda and on the 2030 Agenda and the Sustainable Development Goals (SDGs). This publication checks the progress made in implementing the New Urban Agenda against the SDGs and vice versa. In order to understand the spatial patterns, a national and supranational spatial perspective is taken on some of the SDGs. Given the cross-sectoral nature of cities and communities and their sustainable and resilient development, SDG 11 constitutes an interconnection point and thus covers: Adequate and affordable housing; Level of motorisation and traffic casualties; Land-use and protected landscapes as well as connection to public water supply and waste in its broadest sense. The Federal Institute for Research on Building, Urban Affairs and Spatial Development (BBSR) and the National Institute of Urban Affairs (NIUA) continue with this publication their efforts in identifying and applying a comparable approach to reporting on urban and rural development.
Keywords: Nachhaltige Stadtentwicklung; Entwicklungsziel; Räumliche Disparität; Wohnraumversorgung; Motorisierungsgrad; Flächennutzung; Wasserversorgung; Verkehrsunfall; Schutzgebiet; Sozialindikator; Internationaler Vergleich; Internationale Zusammenarbeit; Sustainable Development Goals; Agenda 2030 für nachhaltige Entwicklung; New Urban Agenda